Análise comparativa dos desfechos epidemiológicos de incidência, mortalidade e letalidade por COVID-19 entre os estados do Espírito Santo e Minas Gerais - Silva, Leonardo Gomes da (2023)
Introduction: in China, in early December 2019, a new type of coronavirus emerged, SARS-CoV-2, a virus that causes a rapidly spreading disease and difficult to control its forms of transmission, given its form transmission is via the respiratory route. COVID19 is a disease that can initially be asymptomatic and can lead to death. Objective: to evaluate the incidence, mortality and lethality rates for COVID-19 between the states of Espírito Santo and Minas Gerais. Methods: this is an ecological study, of a quantitative nature, with time series analysis using a secondary and public database on COVID-19 in the states of Espírito Santo and Minas Gerais, from January 2020 to July of 2022. The incidence and mortality rates, expressed per 100,000 inhabitants, and the lethality rate, expressed as a percentage, were calculated. For trend analyses, Prais-Winsten linear regression was used, where the angular coefficient with its respective probability and the percentage variation of daily change were estimated. All statistical analyzes were performed using the STATA MP 17.0 statistical software. Results: when comparing the incidences of COVID-19 between states, Espírito Santo (ES) has the highest rates, as in 2020, where the rate was 2.19 times higher; in 2021, in which the rate was 1.29 times higher and 2022, corresponding to 2.65 times higher than the state of Minas Gerais. In addition, Espírito Santo had the highest mortality, with the exception of the year 2021. In turn, Minas Gerais had the highest lethality throughout the analyzed pandemic period. Conclusion: it was possible to observe that the state of Espírito Santo had a higher incidence of COVID-19, as well as higher mortality, when compared to the state of Minas Gerais. In turn, Minas Gerais had a higher fatality rate. Furthermore, it was observed that both states showed equal trends for mortality, lethality and incidence in the years 2020 and 2021. For the year 2022, Minas Gerais presents decreasing mortality and incidence and increasing lethality, while the state of Espírito Santo presents a stationary trend for all variables.